Volunteering as a Companion for Foreign Student Exchange in Muhammadiyah University of Parepare - Ainun Arsyad; Eka Puspitasari; Salasiah Ammade (BABASAL English Education Journal, 2023)
In light of globalization in the twenty-first century, graduates need to interact with other cultures to be successful in the international labor market. The author argues that universities need to consider their social relevance in contemporary complex societies. This is a Companion for Foreign Student Exchange in Muhammadiyah University of Parepare.Collaborative learning in cultural exchange: Exploring its current trend and feature. This research method is qualitative, namely taking references from books or from articles that these works for many foreign students face challenges in adjusting to life in their new country. To assist foreign students in overcoming these challenges, volunteering as a companion by applying the STAR (Situation, Challenge, Action, Reflection) method. Volunteering as a co-host on foreign exchange students from Philippines University using the STAR method provides an effective framework for providing support, overcoming challenges, and encouraging reflection. By understanding the situation, identifying challenges, taking appropriate action, and encouraging reflection, volunteer companions provide a holistic and purposeful approach to helping foreign students succeed during their exchange.